The analysis of spatial and functional modifi cations of the palace in Krzesimów in Mełgiew commune aiming at adaptation of the building to the requirements of a social welfare home - Krupa, Karolina; Gleń, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
The palace in Krzesimów was built in the classicist style at the beginning of 19th century. The building is the part of the palace-park complex entered into the register of monuments because of its historical, aesthetical and landscape values. From 1970s, it is the headquarters of a social welfare home. Over the years, this function enforced many changes in the functional layout of the building to adapt it to the needs of people with various types and levels of disability. Despite many minor renovations and modifi cations, the palace didn’t undergo complete overhaul, which would greatly improve the technical condition of the original fabric. This aim of article is to analyse introduced functional changes, which were supposed to facilitate the use of the building by the handicapped, and to consider what actions must be undertaken in order to improve its technical condition. The authors of the paper underline the need to start renovation works on the basis of the archive documentation, as well as conducted survey and research of its current technical condition.